Characterization of dissolved organic material in the interstitial brine of Lake Vida, Antarctica. (15th June 2016) - Cawley, Kaelin M.; Murray, Alison E.; Doran, Peter T.; Kenig, Fabien; Stubbins, Aron; Chen, Hongmei; Hatcher, Patrick G.; McKnight, Diane M.
Abstract: Lake Vida (LV) is located in the McMurdo Dry Valleys (Victoria Valley, East Antarctica) and has no inflows, outflows, or connectivity to the atmosphere due to a thick (16 m), turbid ice surface and cold (<−20 °C) subsurface alluvium surrounding the lake. The liquid portion of LV has a salinity about seven times that of seawater and is entrained in ice and sediment below the ice cap. This subzero (−13.4 °C), anoxic brine supports a microbial community, which has low levels of activity and has been isolated from the atmosphere for at least 2800 14 C years before present. The brine has high dissolved organic carbon concentration (DOC; 580 mg-C L −1 or greater); the study of which provides a unique opportunity to better understand biological and/or abiotic processes taking place in an isolated saline ecosystem with no external inputs. We isolated two sub-fractions of LV dissolved organic matter (DOM) by chemical separation using XAD-8 and XAD-4 resins in series. This separation was followed by physical separation using ultrafiltration to isolate a higher molecular weight (HMW) fraction that was retained by the membrane and a salty, dilute low molecular weight fraction. This analytical path resulted in three, low salt sub-fractions and allowed comparison to other Antarctic lake DOM samples isolated using similar procedures. Compared to other Antarctic lakes, a lower portion of the DOC was retained by XAD-8 (∼10% vs. 16–24%) resin, while the portions retained by XAD-4 (∼8%) resin and the 1 kDa ultrafiltration membrane (∼50%) were similar. The 14 C radiocarbon ages of the XAD-8 (mean 3940 ybp), XAD-4 (mean 4048 ybp) and HMW (mean 3270 ybp) fractions are all older than the apparent age of ice-cover formation (2800 ybp). Ultrahigh resolution mass spectrometry showed that compounds with two and three nitrogen atoms in the molecular formulas were common in both the LV-XAD8 and LV-XAD4 fractions, consistent with microbial production and processing. The long-term oxidation of LVBr DOM by abiotic oxidants including perchlorate and chlorate may explain the low portion in the XAD8 fraction and the lack of aromatic carbon, as measured by 13 C NMR spectroscopy, found for all but the most hydrophobic fraction, LV-XAD8. Overall, the chemical characteristics of Lake Vida brine DOM suggest that legacy DOM sealed and concentrated within the brine has been altered due to a combination of both biological and abiotic chemical reactions.